E-042 Clinical and cost effectiveness of using evolving ace reperfusion catheters as first-line treatment of acute ischemic stroke due to large vessel occlusions. (23rd July 2017) - Kayan, Y; Almandoz, J Delgado; Young, M; Fease, J; Scholz, J; Milner, A; Roohani, P; Mulder, M; Wallace, A; Tarrel, R
Abstract : Introduction: Larger bore reperfusion catheters have been designed to increase the effectiveness of direct aspiration for treatment of acute ischemic stroke due to large vessel occlusions. The present study has two goals: 1. To compare the reperfusion rate of the newest large bore reperfusion catheter, ACE68, with previous generations of ACE catheters, ACE64 and ACE60, and 2. To compare the cost associated with three first-line approaches to mechanical thrombectomy: ADAPT using evolving ACE technology, Solumbra, and stent-retriever (SR) with balloon-guide catheter (BGC). Methods: The prospectively populated acute stroke intervention database at our institution was retrospectively reviewed for mechanical thrombectomies performed using the ADAPT technique as a first-line approach from July 2013 through February 2017. Successful reperfusion (defined as TICI 2b/3) rates amongst the successive generations of ACE reperfusion catheters were compared. The costs of the procedures were also compared, including the costs of salvage therapy using adjunctive devices when necessary (additional reperfusion catheters or SR). These costs were then compared to the costs of hypothetically performing these procedures using Solumbra or SR as first-line approaches. List prices for devices were used in the cost comparison. The two-tailed Fisher's exact test was used for the reperfusion rate comparisons, and Student's t-test was used for the cost comparisons with p<0.05 considered statistically significant. Results: Between July 2013 and February 2017, 131 ADAPT cases were performed using ACE reperfusion catheters. There were 42 cases using the ACE68 as first-line, with a successful reperfusion rate using aspiration alone of 90% (38 of 42). This was significantly higher than with previous generations of ACE as first-line, where the rate of successful reperfusion was 73% using aspiration alone (65 of 89 cases, p=0.02). The rate of successful reperfusion with a single aspiration pass was higher with ACE68 compared to previous generations (50% versus 37%) but this difference was not statistically significant (p=0.19). Overall successful reperfusion was similar when SR was used as salvage therapy (95% with ACE68 as first-line versus 85% with previous ACE generations, p=0.14). Out of 131 patients, 15% (n=20) required the use of SR after aspiration alone, with an improvement to TICI 2b/3 in 13 patients (65%). For ADAPT cases with salvage therapy included, the average device cost per case was not significantly different comparing previous ACE devices with ACE68: $6669 and $6, 650, respectively. An ADAPT approach with any ACE catheter including the cost of salvage therapy resulted in significant cost savings compared to having hypothetically performed these procedures using Solumbra or SR as first-line with costs per case of $12, 440 and $10, 195, respectively, not including salvage therapy. Total costs for all patients for ADAPT, SR, and Solumbra were $866, 150, $1, 325, 350, and $1, 617, 200, respectively. Conclusion: ADAPT with the ACE68 reperfusion catheter resulted in a significantly higher rate of successful reperfusion using aspiration alone (90%) compared to previous generation ACE catheters. ADAPT also resulted in significant cost savings compared to Solumbra or SR first-line approaches. Disclosures: Y. Kayan: 2; C; Medtronic Neurovascular, Penumbra. J. Delgado Almandoz: 2; C; Medtronic Neurovascular, Penumbra. M. Young: None. J. Fease: None. J. Scholz: None. A. Milner: None. P. Roohani: None. M. Mulder: None. A. Wallace: None. R. Tarrel: None.